Kids, raccoons, and roos: awkward encounters and mixed affects. Issue 2 (4th March 2017) - Taylor, Affrica; Pacini-Ketchabaw, Veronica
Abstract : Within the Western cultural imaginary, child–animal relations are characteristically invoked with fond nostalgia and sentimentality. They are often represented as natural and innocent relations, thick with infantilizing and anthropomorphizing 'cute' emotions. Our multispecies ethnographic research – which is conducted in the everyday, lived common worlds of Australian and Canadian children and animals – reveals a very different political and emotional landscape. We find these embodied child–animal relations to be non-innocently entangled, fraught, and messy. In this article, we focus on some awkward encounters of mixed affect when kids and raccoons co-inhabit an urban forest setting in Vancouver, and when kids and kangaroos bodily encounter each other in a bush setting in Canberra. We trace the imbroglio of child–animal curiosities, warinesses, risks, inconveniences, revulsions, attachments, and confrontations at these sites as generative of new ethical logics.